Dialogues and Debates from Late Antiquity to Late Byzantium - Cameron, Averil (Taylor and Francis, 2017)
Cover -- Title -- Copyright -- Contents -- List of contributors -- Acknowledgements -- Introduction -- 1 Plutarch's dialogues: beyond the Platonic example? -- 2 Erostrophus, a Syriac dialogue with Socrates on the soul -- 3 The rhetorical mechanisms of John Chrysostom's On Priesthood -- 4 Literary distance and complexity in late antique and early Byzantine Greek dialogues Adversus Iudaeos -- 5 Prepared for all occasions: the Trophies of Damascus and the Bonwetsch Dialogue -- 6 New wine in old wineskin: Byzantine reuses of the apocryphal revelation dialogue -- 7 Dialogical pedagogy and the structuring of emotions in Liber Asceticus -- 8 Anselm of Havelberg's controversies with the Greeks: a moment in the scholastic culture of disputation -- 9 A Platonising dialogue from the twelfth century: the logos of Soterichos Panteugenos -- 10 The six dialogues by Niketas 'of Maroneia': a contextualising introduction -- 11 Theodore Prodromos in the Garden of Epicurus -- 12 'Let us not obstruct the possible': dialoguing in medieval Georgia -- 13 Embedded dialogues and dialogical voices in Palaiologan prose and verse -- 14 Nikephoros Gregoras's Philomathes and Phlorentios -- 15 Dramatisation and narrative in late Byzantine dialogues: Manuel II Palaiologos's On Marriage and Mazaris' Journey to Hades -- 16 Form and content in the dialogues of Gennadios Scholarios -- Bibliography -- Index.